H2O2 mediates nitrate‐induced iron chlorosis by regulating iron homeostasis in rice. (9th February 2018) - Chen, Haifei; Zhang, Quan; Cai, Hongmei; Zhou, Wei; Xu, Fangsen
Abstract: The uptake of nitrate by plant roots causes a pH increment in rhizosphere and leads to iron (Fe) deficiency in rice. However, little is known about the mechanism how the nitrate uptake‐induced high rhizosphere pH causes Fe deficiency. Here, we found that rice showed severe leaf chlorosis and large amounts of Fe plaque were aggregated on the root surface and intercellular space outside the exodermis in a form of ferrihydrite under alkaline conditions. In this case, there was significantly decreased Fe concentration in shoots, and the Fe deficiency responsive genes were strongly induced in the roots. The high rhizosphere pH induced excess hydrogen peroxide (H2 O2 ) production in the epidermis due to the increasing expression of NADPH‐oxidase respiratory burst oxidase homolog 1, which enhanced root oxidation ability and improved the Fe plaque formation in rhizosphere. Further, the concentrated H2 O2 regulated the phenylpropanoid metabolism with increased lignin biosynthesis and decreased phenolics secretion, which blocked apoplast Fe mobilization efficiency. These factors coordinately repressed the Fe utilization in rhizosphere and led to Fe deficiency in rice under high pH. In conclusion, our results demonstrate that nitrate uptake‐induced rhizosphere alkalization led to Fe deficiency in rice, through H2 O2 ‐dependent manners of root oxidation ability and phenylpropanoid metabolism. Abstract : Rice prefers ammonium not nitrate, and high pH induces plant iron deficiency, but the relationship and its mechanism are poorly understood. Here, we found that the preference of rice for ammonium relative to nitrate is tightly related to the external pH of the growth environment, and the nitrate uptake‐induced rhizosphere alkalization caused rice iron deficiency and growth inhibition. In this case, the accumulated hydrogen peroxide mediated nitrate‐induced iron deficiency, which acted as a crucial signal involved in iron homeostasis by regulating iron plaque formation and apoplastic iron mobilization under high pH environments. Accumulated H2 O2 regulates nitrate‐induced Fe deficiency.